The role of defendable space as a key urban design tool for bushfire risk management - Kornakova M; March A (Massey University)
Changes in climatic conditions around the world associated with anthropogenic climate change have result in increased numbers of extreme weather events. Population growth, migration, urban sprawl and tree change movements are often combined with peoples’ desire to live near beneficial natural assets such as water bodies, elevated slopes or forests. Accordingly, these events are increasingly leading to disasters that cause significant damage to human settlements, injury or loss of life. This is particularly evident in the Australian context, where the increased frequency of extreme weather has led to greater numbers of bushfires. Given that fire will continue to be integral to Australia’s natural landscape, there is an ongoing need to develop tools for managing the risks associated with bushfires.